The Anesthesia Preoperative Evaluation Clinic (APEC): a prospective randomized controlled trial assessing impact on consultation time, direct costs, patient education and satisfaction with anesthesia care - Schiff, Jan-Henrik; Frankenhauser, Susanne; Pritsch, Maria; Fornaschon, S. A.; Snyder-Ramos, Stephanie; Heal, C.; Schmidt, Karsten; Martin, E.; Böttiger, B. W.; Motsch, Johann (Minerva Anestesiologica, 2010)
Anesthetic preoperative evaluation clinics (APECs) are relatively new institutions. Although cost effective, APECs have not been universally adopted in Europe. The aim of this study was to compare preoperative anesthetic assessment in wards with an APEC, assessing time, information gain, patient satisfaction and secondary costs.
Gesehen am 06.06.2023